2023
DOI: 10.3390/plants12152823
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Total Isoflavones in Chickpea (Cicer arietinum L.) Sprouts Germinated under Precursors (p-Coumaric Acid and L-Phenylalanine) Supplementation

Jaya Arora,
Bhanupriya Kanthaliya,
Abhishek Joshi
et al.

Abstract: Cicer arietinum L. (Bengal gram, chickpea) is one of the major pulse crops and an important part of traditional diets in Asia, Africa, and South America. The present study was conducted to determine the changes in total isoflavones during sprouting (0, 3, and 7 days) along with the effect of two precursor supplementations, p-coumaric acid (p-CA) and L-phenylalanine (Phe), in C. arietinum. It was observed that increasing sprouting time up to the seventh day resulted in ≈1282 mg 100 g−1 isoflavones, which is app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 76 publications
4
4
0
Order By: Relevance
“…At the same time, there was shown no change in water content using the example of Carthamus tinctorius seedlings in the presence of the indicated above precursor [ 28 ]. It is worth noting that for Phe, a similarity to our data effect was noted for the Vitex agnus castus shoot cultures and Cicer arietinum seedlings [ 29 , 30 ]. While the Cin effect on the example of Pisum sativum was the opposite and revealed in a decrease in water content [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…At the same time, there was shown no change in water content using the example of Carthamus tinctorius seedlings in the presence of the indicated above precursor [ 28 ]. It is worth noting that for Phe, a similarity to our data effect was noted for the Vitex agnus castus shoot cultures and Cicer arietinum seedlings [ 29 , 30 ]. While the Cin effect on the example of Pisum sativum was the opposite and revealed in a decrease in water content [ 31 ].…”
Section: Discussionsupporting
confidence: 84%
“…On the example of Cicer arietinum leaves and Sequoia sempervirens callus culture, the increase in its content was shown in the presence of Phe, which was similar to our data [35]. While in the cells of the Moringa oleifera plant this trend was significantly less pronounced, herewith in quinoa sprouts there was no statistically significant difference between the experimental and control variants [30,46]. There are data confirming the increase in the accumulation of PCs in Carthamus tinctorius and Vigna radiata seedlings in the presence of Nar, while in the first case this indicator increased almost two-fold [27,28].…”
Section: The Low-molecular Antioxidants In Tea Cells Culturessupporting
confidence: 90%
“…In the current study, we report phytochemical analysis and antioxidant assays on different parts (leaf, stem, and bark) of G. senegalensis for the first time. Conclusively, the antioxidant role played by various secondary metabolites such as phenols, flavonoids, tannins, etc., reported in various studies showed ROS inhibition, lipid peroxidation, platelet aggregation, membrane stabilization, restoration of vascular function, and antioxidant enzymes [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another group of bioactive compounds evaluated in this SI was isoflavones. Arora et al studied the total isoflavone content in chickpea (Cicer arietinum L.) sprouts, germinated under precursors such as p-coumaric acid and L-phenylalanine [11]. The authors observed that an increase in sprouting time for a period up to seven days resulted in isoflavone content that was approximately eight times higher than that in chickpea seeds.…”
Section: An Overview Of the Simentioning
confidence: 99%